Walden ; and On the duty of civil disobedience [compact disc, unabridged] - Thoreau, Henry David, 1817-1862 (Blackstone Audio, Inc., 2009)
In 1845 Thoreau built himself a shanty in the woods by Walden Pond, where he lived from 1845-1847. Walden is a treatise on the subjects of self-sufficiency, individualism, relationship with nature, and rejection of material ambition. His residence at the pond was interrupted by a day's imprisonment for refusal to pay a poll tax to a government that supported the Mexican War. This action was in accord with his belief in passive resistance, a means of protest he explained in his essay "Civil Disobedience (1849).